Affecting Factors Of The Exclusive Breastfeeding Giving In The Public Health Center Workplace At Lingkar Timur In Bengkulu City Year 2017 - Elly Wahyuni; Serilaila Serilaila; Donna Rahmiati (Politeknik Kesehatan Kemenkes Jakarta II, 2018)
The coverage of exclusive breastfeeding in Indonesia is still low, in 2007 32%, in 2012 27.1%. Likewise Bengkulu Province, especially in East Circle Health Center 45.1% while the national target of 80%. Many factors affect the exclusive breastfeeding of knowledge, age, motivation, employment and promotion of infant formula. The purpose of this study was to determine the factors that influence exclusive breastfeeding. This research was conducted by cross sectional method in mothers who have babies aged 7-12 months totaling 106 respondents (total sampling). Locations in Working Area Puskesmas Lingkar Timur on May-June 2017. Data were collected univariate, bivariate and multivariate analyzes using Chi Square test and multivariate logistic regression test. Results: a study of 106 mothers with babies 56.6% did not give exclusive breastfeeding, 57.5% less knowledge, 66.0% age 20-35 years, 80.2% high motivation, 59.4% working mothers, 67 , 0% are not exposed to the promotion of formula milk. (P = 0,00 RP = 5,60) and promotion of infant formula (p = 0.00 RP = 8.20) is associated with exclusive breastfeeding, whereas the age variable (p = 0.27 RP = 1.57) is not associated with exclusive breastfeeding. The most dominant factor is knowledge (p = 0,00 Exp (B) = 15,909). Suggestion: It is expected to improve exclusive breastfeeding, health workers should establish breastfeeding mothers' classes with more intensive counseling. And the need for policies to provide appropriate sanctions against violations.